ANALYSIS OF THE INFLUENCE OF WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLES (Case Study at Swasti Sari Cooperative Branch of Kefamenanu) - Elfrida Desiderata Naihati (Jurnal Ekonomi, 2022)
This study aims to determine the partial effect of the variables Work Motivation (X1) and Job Satisfaction (X2) on Employee Performance (Y) and Organizational Commitment (X3) as intervening variables. The data used in this study are primary data obtained through questionnaires which were distributed to 32 respondents. The data analysis technique used is descriptive analysis and inferential analysis, namely Path Analysis with the help of SPSS 20.0 software with the following analysis results: There is a positive influence of work motivation (X1) on employee performance (Y) Kopdit Swasti Sari Kefamenanu Branch . This is evidenced by the calculated t value of 2.092, a significance value of 0.046 <0.05; and a regression coefficient of 0.280. There is an effect of job satisfaction (X2) on employee performance (Y) Kopdit Swasti Sarri Kefamenanu Branch. This is evidenced by the calculated t value of 3.152, a significance value of 0.004 <0.05; and a regression coefficient of 0.489. There is no positive effect of organizational commitment on employee performance (Y) Kopdit Swasti Sari Kefamenanu Branch. This is evidenced by the calculated t value of 806 <1.669, a significance value of 0.427 > 0.05; and a regression coefficient of 0.130. There is a positive influence of work motivation (X1) on organizational commitment (X3). This is evidenced by the calculated t value of 2.187, a significance value of 0.037 <0.05. There is a positive effect of job satisfaction (X2) on organizational commitment (X3). This is evidenced by the calculated t value of 3.572, a significance value of 0.001 <0.05. Based on the results of the analysis using the path analysis tool, there is no positive effect of work motivation (X1) on employee performance (Y) with organizational commitment as an intervening variable. This is evidenced by the direct effect which is greater than the indirect effect, namely 0.389 > 0.049. There is no positive effect of job satisfaction (X2) on employee performance (Y) with organizational commitment (X3) as the intervening variable. This is evidenced by the direct effect which is greater than the indirect effect, namely 0.650 > 0.080